Pemberdayaan Literasi Keuangan Untuk Meningkatkan Kesejahteraan Keluarga Penerima Manfaat Program Keluarga Harapan (PKH) - Widyadhana, Kevin Naufal; Rachmawati, Nurendah Shinta; Warsidi, Warsidi (Prisani Cendekia, 2024)
Financial literacy plays a crucial role in improving the economic well-being of communities, especially for beneficiaries of the Family Hope Program (PKH). However, low financial literacy remains a challenge, particularly in rural areas. This community engagement program aims to enhance the financial management knowledge of residents in Tanjungbaru Village through socialization and financial education. The methods used include pre-tests, interactive counseling, and post-tests to measure program effectiveness. The material covered income recording, expense calculation, budgeting, debt management, and the importance of emergency funds. The results showed improved participants' understanding of financial literacy concepts, as reflected in the increased post-test scores. Through this financial education initiative, the community is to manage their finances better, avoid excessive debt, and plan long-term financial goals to improve family well-being. Continuous financial education is necessary to ensure sustainable financial literacy growth and positive economic impacts.